2017
DOI: 10.1186/s13071-017-2415-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal genetic differentiation in Glossina pallidipes tsetse fly populations in Kenya

Abstract: Background Glossina pallidipes is a major vector of both Human and Animal African Trypanosomiasis (HAT and AAT) in Kenya. The disease imposes economic burden on endemic regions in Kenya, including south-western Kenya, which has undergone intense but unsuccessful tsetse fly control measures. We genotyped 387 G. pallidipes flies at 13 microsatellite markers to evaluate levels of temporal genetic variation in two regions that have been subjected to intensive eradication campaigns from the 1960s to the 1980s. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 71 publications
1
24
1
Order By: Relevance
“…Effective population sizes obtained in Kenya with temporal methods (N e ≈ 100-2,000), a method for which we did not have appropriate sampling, suggests much bigger G. pallidipes densities (Okeyo et al, 2017;Ouma et al, 2006) than what we found, unless tsetse subpopulations in Kenya occupy larger surfaces as compared to Tanzania. Nevertheless, in these studies, superficial analyses of heterozygote deficits causes and/or the use of pooling of some of the available subsamples makes any comparison quite uneasy.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Effective population sizes obtained in Kenya with temporal methods (N e ≈ 100-2,000), a method for which we did not have appropriate sampling, suggests much bigger G. pallidipes densities (Okeyo et al, 2017;Ouma et al, 2006) than what we found, unless tsetse subpopulations in Kenya occupy larger surfaces as compared to Tanzania. Nevertheless, in these studies, superficial analyses of heterozygote deficits causes and/or the use of pooling of some of the available subsamples makes any comparison quite uneasy.…”
Section: Discussioncontrasting
confidence: 70%
“…The reversed relation when more than 40% pairs of loci are in LD comes from the same mechanism described in a previous paper (Prugnolle & De Meeûs, 2010) (Ouma, Marquez, & Krafsur, 2005). Isolation by distance was never accurately explored in the literature for this species, either because it was not really studied (Ouma et al, , 2005Ouma, Marquez, & Krafsur, 2006) or because it was analyzed with temporally heterogeneous subsamples (Okeyo et al, 2017). Clade B contained few and very small subsamples and the differences observed with Clade A might not be significant.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…38 Previous work has also shown that G. pallidipes populations undergo temporal changes in allele frequencies because of both natural (such as seasonal environmental fluctuations), and humaninduced factors (such as control measures). 42 Nonetheless, there remain gaps in our knowledge of the population structure of this dangerous vector in Kenya, especially at a regional scale.…”
Section: Introductionmentioning
confidence: 99%